Particulate products : tailoring properties for optimal performance - Merkus, Henk G.; Meesters, Gabriel M. H., 1962- (Cham : Springer, 2014)
Particulate products make up around eighty percent of chemical products, from all industry sectors. Examples given in this book include construction materials, fine ceramics and concrete, chocolate and ice cream, pharmaceutical, powders, medical inhalers and sun screen, liquid and powder paints. Size distribution and the shape of the particles provide for different functionalities in these products, some general some specific. This book addresses particle packing as well as its relation to powder flow and rheological behavior. Moreover, general relationships to particle size are discussed for e.g. color and sensorial aspects of particulate products. The book covers all the particulate aspects that are most relevant for behavior and performance within specified industrial products and how optimal results can be obtained. It differs from other books in the way that the critical aspects of different products are reported, so that similarities and differences can be identified. Contributors to this book are acknowledged experts coming from a wide range of different product industries. The aim of the book is to lead to improved optimization in design, development and quality of many particulate products.
Includes bibliographical references and index.
Keywords: Particles; Chemical engineering